The Role of Class Point Website in Learning English Vocabulary Mastery Among Indonesian Junior High School Students - Nur Kameliya, Isnaini; Sofian Hadi, Muhammad (Ikatan Da'i Indonesia, 2025)
This study investigates the role of the Class Point website in improving English vocabulary mastery among Indonesian junior high school students. The study was motivated by the increasing importance of integrating digital learning media into English language classrooms to promote engagement and active learning. Employing a quantitative quasi-experimental design, this research involved 48 eighth-grade students from MTs Al-Falah Jakarta, divided into an experimental group and a control group. The experimental group was taught using Class Point, while the control group received conventional instruction. The data were collected using pre-tests, post-tests, and a perception questionnaire. The findings indicated a significant difference between both groups, with the experimental group achieving higher post-test scores (M = 86.67) compared to the control group (M = 75.96), and a t-value of 4.289 (p < 0.05). Students’ perception results also revealed a positive response (M = 4.23), suggesting that Class Point enhances motivation and participation in vocabulary learning. Therefore, it can be concluded that the Class Point website is an effective digital learning tool for improving English vocabulary mastery among junior high school students.